AKULTURASI HUKUM ISLAM DAN TRADISI LOKAL BEN-GHIBEN DALAM PERNIKAHAN DI KABUPATEN BANGKALAN-MADURA - Masrokhin Masrokhin; Mariyatul Qibtiyah (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of qualitative field research with an Islamic legal sociology approach. This article discusses the ben-ghiben tradition in Madurese traditional marriage. Several series of traditions that exist in the implementation of the ben-ghiben tradition contain acculturation between Islamic law and customary law that strengthen each other. The researcher uses 'urf analysis in explaining the legal position of ben-ghiben. 'Urf is flexible and adaptive in determining the legal status of localistic things. The location of this research is in Bangkalan village, Madura. This study concludes that the ben-ghiben tradition in Bangkalan village, Madura is permissible because it does not conflict with the theory of urf which is prohibited in the study of usul fiqh. Keywords: acculturation of Islamic law, ben-ghiben tradition, wedding customs in kabupaten Bangkalan